Modern documentary film production requirements - Yegemberdiyev, Ы.Д.; Turzhan, О.І.; Ibrayeva, Э.Е. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
The article discusses features of a documentary film, modern methods of production of a documentary film, the main stages of film production, the structure of technical and visual elements. The article focuses on professional requirements for documentary films producers as well as the direction of documentary films, and features of the text of the modern screenplay. The article analyzes the importance of titles in a documentary film as a separate art. The authors relied on the scientific and conceptual works of documentary filmmakers and film researchers when studying this field. The study is based on the successful experience of films production by such documentary filmmakers as V. Shklovsky, H. Zaypel, L. G. Parfenov.